2021
DOI: 10.1126/science.abb6848
|View full text |Cite
|
Sign up to set email alerts
|

Tissue regeneration: Reserve or reverse?

Abstract: Stem cells recover from injury by tissue dedifferentiation, not from dedicated reserves

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…A recent study has suggested that under conditions of chemical ablation, the partially differentiated cells of the inner enamel epithelium in the mouse incisor may revert to progenitor cells (Sharir et al, 2019). This idea that tissues can regenerate even if the local stem cell population is almost depleted has been demonstrated in the intestine and other organs (Gola and Fuchs, 2021;Shivdasani et al, 2021).…”
Section: Two Interpretations Of Brdu-labeled Cells -Dedifferentiation Versus Stem/progenitor Cellsmentioning
confidence: 99%
“…A recent study has suggested that under conditions of chemical ablation, the partially differentiated cells of the inner enamel epithelium in the mouse incisor may revert to progenitor cells (Sharir et al, 2019). This idea that tissues can regenerate even if the local stem cell population is almost depleted has been demonstrated in the intestine and other organs (Gola and Fuchs, 2021;Shivdasani et al, 2021).…”
Section: Two Interpretations Of Brdu-labeled Cells -Dedifferentiation Versus Stem/progenitor Cellsmentioning
confidence: 99%
“…Many types of intestinal cells at intermediate or even terminal differentiation stages can dedifferentiate following a lethal injury in normal tissues to replenish the SC repertoire, or as a consequence of the acquisition of genetic alterations and/or in response to signals from the tumor microenvironment in cancer. Thus, stemness is today considered a modifiable cellular state instead of a permanent feature of a fixed group of normal or cancer cells [ 61 , 62 , 63 ]. Two simultaneous studies using CRISPR-Cas9 to label (with GFP) and then eliminate LGR5 + CSC (by means of knock-in Caspase 9 or diphtheria toxin receptor cassettes) smartly demonstrated the plasticity of human and mouse CRC CSC [ 64 , 65 ].…”
Section: Organoids As a Model To Study Crcmentioning
confidence: 99%
“…This is likely enabled by the epigenetic similarities between various crypt populations and ISCs (62, 68), as well as the presence of redundant niche sources (20,21,28,69), which may allow more differentiated types to revert to the stem cell state with relative ease upon encountering the right stimuli. Interestingly, under this model, one could argue that any devoted reserve stem populations would become dispensable; indeed, the most recent studies suggest that de-differentiation (followed by subsequent upregulation of the ISC master regulator Ascl2) can satisfactorily explain intestinal epithelial regeneration upon initial loss of Lgr5+ ISCs (70,71). However, this also constitutes a highly controversial issue, with radioresistant and other potential reserve stem cell populations remaining very possible, as these are not necessarily mutually exclusive models (72,73).…”
Section: Approachesmentioning
confidence: 99%